Leveraging Ed-tech in the Co-curricular Space: Reflections on Design and Development Aspects of the Class Representative Induction Programme at the University of Cape Town (Journal of Student Affairs in Africa, 2021)
Every year, class representatives are elected at the University of Cape Town to represent students on academic matters in relation to a specific academic course. A vital element of this representative role is to advocate for an enabling learning environment that promotes learning excellence. In preparing class representatives for their leadership roles, the Department of Student Affairs, in partnership with the Students’ Representative Council (SRC) and the Faculty Councils, host and facilitate a class representative induction programme. The induction typically utilised face-to-face synchronous teaching methods. However, since the advent of Covid-19, adaptions to the induction programme had to be made in order to reflect the new normal imposed by the pandemic. Against this backdrop, this article addresses various design-related choices encountered from an online education technology perspective. Key areas of reflection include working with the SRC Undergraduate Academic Co-ordinator and Faculty Councils as a design team in transitioning a, hitherto, synchronous programme catering for approximately 420 class representatives, from a face-to-face mode of delivery to an online mode of delivery. Particular attention is paid to the social constructivist design elements of the programme development process and how these elements were managed with regards to the enablements and constraints encountered in the virtual space by exploring the technological affordances of various ed-tech options available to student affairs practitioners. This article contributes to the practitioner literature by demonstrating how ed-tech can be leveraged to aid in the preservation of existing practices as blended learning approaches continue to shape and augment the future of co-curricular programme delivery in higher education.
Keywords: blended learning; leadership development; online co-curricular programmes; online learning design; participatory curriculum development